Synthesis, molecular docking, and ADME analysis of a series of 4-amino-3,5-dimethyl-1,2,4-triazole derivatives - L. I. Kucherenko; T. S. Brytanova; A. S. Hotsulia (Zaporozhye State Medical University, 2023)
The heterocyclic system of 1,2,4-triazole enables the successful creation of promising biologically active compounds. By creating a range of derivatives based on 4-amino-3,5-dimethyl-1,2,4-triazole, the spectrum of potential biologically active compounds can be expanded. The aim of the work was the synthesis and in silico justification of the prospects for the search for biologically active compounds among 4-amino-3,5-dimethyl-1,2,4-triazole derivatives. Materials and methods. The work uses modern methods for synthesizing organic compounds, followed by confirmation of their individuality and structure through the analysis of physical-chemical parameters and spectroscopic techniques such as 1H NMR, IR spectroscopy, elemental analysis, and chromatography-mass spectrometry. To assess the similarity of the synthesized compounds to medicinal products, the SwissADME online tool was employed. The probability of impact on a number of enzyme systems (cyclooxygenase-2, lanosterol 14α-demethylase, anaplastic lymphoma kinase) was estimated using molecular docking. Results. A series of newly synthesized derivatives of 4-amino-3,5-dimethyl-1,2,4-triazole was obtained, and the synthesis conditions were optimized and their structures were confirmed. It was determined that there is a high probability of influencing lanosterol 14α-demethylase, highlighting the significance of further research on the antifungal activity of the synthesized compounds. Additionally, the potential influence on the activity of cyclooxygenase-2 and anaplastic lymphoma kinase was discovered. However, the probability of exhibiting the corresponding activities, namely anti-inflammatory and anti-cancer, is low. Physical indicators, parameters of pharmacokinetics, and drug-likeness are important, which determines the prospects of creating biologically active substances based on the synthesized series of compounds. Conclusions. A series of 4-((R-iden)amino)-3,5-dimethyl-1,2,4-triazoles were synthesized, and their general physical-chemical properties were determined. The overall potential for creating innovative biological products based on these compounds was assessed using in silico methods for predicting the activity of substances.